Dissecting executive dysfunction in children: The role of psychosocial disabilities through Bayesian and ANOVA approaches - Soo Eun Chae (PLoS ONE, 2026)
This study investigates the relationship between executive dysfunction and psychosocial disabilities in children aged 8–11, utilizing data from the Korean Child Panel Study collected between 2015 and 2018. The dataset, consisting of 1,196 valid responses, was analyzed using a Latent Growth Model, which revealed that a quadratic model best fit the data. Results indicated that executive dysfunction scores plateaued until age 10 before slightly declining. Children with psychosocial disabilities showed significantly higher levels of executive dysfunction than their peers without such disabilities, with a notable increase over time. We compared the average executive dysfunction levels between children with no psychosocial disorders (N = 1,174) and those with psychosocial disorders (N = 22) using repeated measures ANOVA. To address the small sample size of the psychosocial disorders group, both Bayesian repeated measures analysis and repeated measures ANOVA were performed. The ANOVA identified significant interaction and main effects, while the Bayesian analysis highlighted significant main effects. This discrepancy underscores the need for nuanced methodologies when dealing with small populations. The study confirms a positive correlation between psychosocial disabilities and executive dysfunction observed internationally, emphasizing its relevance to Korean children. These findings underscore the importance of early recognition and intervention for children with psychosocial and cognitive difficulties.